THE INFLUENCE OF MEME CULTURE ON THE PERCEPTION OF JAPANESE MUSIC: A SURVEY OF DOLPHIN IN TOWN-KINGO HAMADA - Alfajri, Salsabila; Wibawarta, Bambang (UI Scholars Hub, 2025)
The research aims to explore the influence of meme culture on the perception of Japanese music in the digital era, specifically analyzing the impact of meme culture on the song